Endoscopic Closure of Large Iatrogenic Duodenal Perforation: Right Use of Endoscopic Accessories - Kumar, Naveen; Srinu, Deshidi; Kakadiya, Rinkal; Kurdia, Kailash Chand; Jearth, Vaneet; Shah, Jimil (Journal of Digestive Endoscopy, 2022)
Perforations during endoscopic retrograde cholangiopancreatography (ERCP) is a rare but dreadful complication. Type I Stapfer's perforations tend to be large and can get easily complicated by peritonitis and collections if not recognized and managed in a timely manner. With advancement in endoscopic accessories, endoscopic closure is usually attempted first, and surgical interventions are reserved only in patients with a failed endoscopic attempt. Though over the scope clips (OTSC) are used in patients with defect up to 20 to 25 mm in gastric or duodenal perforation and up to 30 mm in colonic perforations, larger defects can be also closed with the right use of adjuvant accessories. Here, we report our experience of successful closure of a large duodenal perforation during ERCP, using a single OTSC clip with help of accessories.
Keywords: conservative; endoscopy; OVESCO